Pendidikan Akhlak dalam Kitab Ighātsatul Lahfān Karya Ibnul Qayyim Al-Jauziyyah: Analisis Konsep dan Implikasinya dalam Pendidikan Islam - Tena Agustina; Syarif Maulidin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study is motivated by the decline in students’ moral character, as reflected in weak academic honesty, decreasing respect for teachers, and limited social responsibility in educational environments. These symptoms indicate that educational practices often emphasize academic achievement more than moral and spiritual formation. This study aims to analyze the concept of diseases of the heart as the foundation of moral education according to Ibnul Qayyim al-Jauziyyah in Ighātsatul Lahfān and to examine its implications for Islamic education. This research uses a qualitative approach with library research and content analysis. The primary source is Ighātsatul Lahfān, while secondary sources consist of books, journal articles, and relevant studies on moral education, Islamic education, and character formation. The findings show that morality is rooted in the condition of the heart as the center that directs human behavior. Diseases of the heart in the forms of syubhat and syahwat become major causes of moral degradation. Tazkiyatun nafs serves as the main process of moral development through purification of the soul, habituation of worship, self-control, reflection, and strengthening spiritual awareness. A heart-centered educational approach remains relevant for contemporary Islamic education because it integrates intellectual development, spiritual cultivation, and moral practice in the formation of students’ character.